PENERAPAN MODEL CTL UNTUK MENINGKATKN PENGUASAAN KOSAKATA DAN PEMAHAMAN MEMBACA TEKS SEDERHANA BAHASA INGGRIS PADA SISWA KELAS V SEKOLAH DASAR: PENERAPAN MODEL CTL UNTUK MENINGKATKN PENGUASAAN KOSAKATA DAN PEMAHAMAN MEMBACA TEKS SEDERHANA BAHASA INGGRIS PADA SISWA KELAS V SEKOLAH DASAR - Putri Jannati; Galih Putri Pertiwi (Al-Azkiya: Jurnal Pendidikan MI/SD, 2026)
The objective of this research is to examine the efficacy of the Contextual Teaching and Learning (CTL) approach in enhancing fifth-graders' vocabulary acquisition and English reading skills at MI Al-Ashriyah Langsa during the 2025/2026 school year. The research employed a quantitative approach with a one-group pretest-posttest design. The participants consisted of 25 students. This study utilized a quantitative method with a one-group pretest-posttest design, involving a sample of 25 students. To evaluate the impact of the CTL model, data were gathered through vocabulary and reading comprehension assessments conducted both prior to and following the intervention. Statistical analysis was performed through normality and homogeneity testing, followed by a paired sample t-test and N-Gain Score evaluation. The results revealed a substantial enhancement in students' vocabulary proficiency, as evidenced by a mean score increase from 47.20 to 71.60. Furthermore, the N-Gain score of 0.46 places this improvement within the moderate category. In a similar vein, reading comprehension scores rose from 49.60 to 74.80, yielding an N-Gain of 0.50, which falls into the moderate classification. The paired sample t-test resulted in a significance level of 0.000 (p < 0.05), confirming a statistically significant disparity between the pretest and posttest outcomes. Consequently, these findings validate the efficacy of the CTL model in boosting English achievement among primary schoolers, particularly in vocabulary acquisition and basic text comprehension.